Alumni of University EFL Students’ Opinions about Register of Football - Arifin Kurniawan (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2021)
The existence of football has paved the way for this study to find the football registers types. This linguistic part explains about language and the usage. The researcher implemented the theories of register from Biber and Conrad (2009) and Biber and Finegan(1994). This investigation uses the interviews via whatsApp to gather the data from 5 participants. These people were the alumni from university located in Yogyakarta. After the information of interview is got, the researcher analyzed it. The results showed 16 types as follows. First finding is actions. Second result shows positions. Third finding reveals places. Fourth result is championships. Fifth finding is supporters types. Sixth result reveals clubs. Seventh finding shows tools. Eighth result has business in football. Nineth finding is referee types. Tenth result indicates impacts of fouls. Eleventh finding is special matches. Twelveth result shows times. Thirteenth finding reveals honorifics. Fourteenth result has name. Fifteenth finding is impacts of less achievements. Sixteenth result has formations.